2019
DOI: 10.12688/wellcomeopenres.15140.1
|View full text |Cite
|
Sign up to set email alerts
|

HPV infection and pre-term birth: a data-linkage study using Scottish Health Data

Abstract: Background: We aimed to investigate whether infection with high-risk (HR) types of human papilloma virus (HPV) or HPV-associated cervical disease were associated with preterm birth (<37 weeks gestation). In a sub-group of younger women who were eligible for the HPV vaccine, we aimed to determine whether prior vaccination against the specific HPV-types, HPV-16 and -18 modified preterm birth risk. Methods: This was a data-linkage study, which linked HPV-associated viral and pathological information (from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…Previous studies have presented conflicting results. A recent population-based study did not confirm an increased risk of PTD in women positive for high-risk HPV without CIN2+ (aOR 1.11, 95% CI 0.75–1.66) [ 20 ], perhaps due to a lack of power based on the much smaller sample. The risk estimates in our study (aOR 1.21 for cytology and aOR 1.19 for HPV test) were slightly lower than that suggested by a recent meta-analysis (aOR 1.50), but within the 95% CI of that study (1.19–1.88) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have presented conflicting results. A recent population-based study did not confirm an increased risk of PTD in women positive for high-risk HPV without CIN2+ (aOR 1.11, 95% CI 0.75–1.66) [ 20 ], perhaps due to a lack of power based on the much smaller sample. The risk estimates in our study (aOR 1.21 for cytology and aOR 1.19 for HPV test) were slightly lower than that suggested by a recent meta-analysis (aOR 1.50), but within the 95% CI of that study (1.19–1.88) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is thus unknown whether HPV infection can cause PTD or other adverse obstetric outcomes. Studies linking positive HPV tests and/or abnormal cervical cytology with obstetric outcomes have shown conflicting results [18][19][20][21]. A recent meta-analysis and systematic review suggested an association between HPV infection and PTD, and possibly pPROM [22], although all included studies were small.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these hypotheses, not all studies have proven this association. Contributing to controversy in the field is Aldhous' recent data-linkage study, which found that high-grade cervical lesions due to HPV increased the risk of preterm birth, but not HPV infection alone [85]. Moreover, in their prospective case-control study carried out on 271 patients, Ambühl et al found no link between placental HPV, regardless of type, and spontaneous preterm labor [97].…”
Section: Preterm Birthmentioning
confidence: 99%
“…Infectious pathogens during pregnancy have repeatedly been indicated to be responsible for adverse pregnancy outcomes, as well as a number of severe neonatal sequelae [82]. However, the involvement of HPV in the evolution and outcome of pregnancy is not quite clear, with studies reporting somewhat contradictory results: while some authors saw no relationship [83,84], others highlighted various adverse pregnancy outcomes, ranging from preterm birth [85], spontaneous abortion [86], the premature rupture of membranes [87], and pregnancy-induced hypertensive disorders [88] to intrauterine growth restriction [89], low birth weight [90], and fetal death [88]. A degree of contradiction between studies is, nevertheless, to be expected, if one takes into consideration the different sizes of the study samples, the more or less rigorous methodology, and the occasional lacking values for different variables (Table 2).…”
Section: Hpv and Pregnancy Outcomesmentioning
confidence: 99%
“…14 Several linkages of clinical maternity and infant data have nonetheless shown the feasibility of the approach and usefulness, for example, in aligning hospital maternity data with national birth registration datasets, or birth registration datasets with Hospital Episode Statistics (HES), or using UK primary care pregnancy data to create a pregnancy register. [15][16][17][18][19][20][21][22][23][24][25] It is well established that maternal physical and mental well-being in pregnancy and the postpartum period can strongly influence the neonatal outcome and the physical and mental health of the child. [26][27][28][29] To our knowledge, no clinical data linkages in maternity or neonatal services have to date incorporated clinical information from maternity, neonatal and mental health services into a single continuum to interrogate these associations at a population level.…”
Section: Introductionmentioning
confidence: 99%